PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BAMBOO DANCING (TARI BAMBU) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMAN 3 PEKANBARU - Susi Lestari; Rasmiwetti '; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research about application of bamboo dancing cooperative learning model aims to improve students learning achievement on the subject of hydrocarbon in class X SMAN 3 Pekanbaru. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes, which are X8 as experiment class and X9 as control class that randomly selected after testing normality and homogeneity. Experiment class was given treatment with implementing bamboo dancing cooperative learning model while the control class wasnot given treatment bamboo dancing cooperative learning model. Analysis of data used t-test. Results of the analysis it was found that tscore > ttable (4,60 > 1,67), it means that the application bamboo dancing cooperative learning model can improve students achievement on the subject of hydrocarbon in class X SMAN 3 Pekanbaru. The category improvement of students learning achievement in experiment class was high category (N-gain =0,76) and in control class was medium category (N-gain =0,63).Key Words : Bamboo Dancing Cooperative Learning Model, Learning Achievement, Hydrocarbon